Preclinical dosimetry in proton minibeam radiation therapy: Robustness analysis and guidelines. Issue 8 (8th June 2022) - Ortiz, Ramon; De Marzi, Ludovic; Prezado, Yolanda
Abstract: Purpose: Proton minibeam radiation therapy (pMBRT) is a new radiotherapy approach that has shown a significant increase in the therapeutic window in glioma‐bearing rats compared to conventional proton therapy. The dosimetry of pMBRT is challenging and error prone due to the submillimetric beamlet sizes used. The aim of this study was to perform a robustness analysis on the setup parameters utilized in current preclinical trials and provide guidelines for reproducible dosimetry. The results of this work are intended to guide upcoming implementations of pMBRT worldwide, as well as pave the way for future clinical implementations. Methods: Monte Carlo simulations and experimental data were used to evaluate the impact of variations in setup parameters and uncertainties in collimator specifications on lateral pMBRT dose distributions. The value of each parameter was modified individually to evaluate their effect on dose distributions. Experimental dosimetry was performed by means of high‐resolution detectors, that is, radiochromic films, the IBA Razor and the Microdiamond detector. New guidelines were proposed to optimize the experimental setup in pMBRT studies and perform reproducible dosimetry. Results: The sensitivity of dose distributions to uncertainties and variations in setup parameters was quantified. Quantities that define pMBRT lateral profiles (i.e., the peak‐to‐valley dose ratio [PVDR], peak and valley doses, and peak width) are significantly influenced by small‐scale fluctuations in several of those parameters. The setup implemented at the Orsay proton therapy center for pMBRT irradiation was optimized to increase PVDRs and peak symmetry. In addition, we proposed guidelines to perform accurate and reproducible dosimetry in preclinical studies. Conclusions: This study revealed the importance of adopting guidelines and protocols tailored to the distinct dose delivery method and dose distributions in pMBRT. This new methodology leads to reproducible dosimetry, which is imperative in preclinical trials. The results and guidelines presented in this manuscript can ease the initiation of pMBRT investigations in other centers.